Knowledge Creation between Integrated Assessment Models and Initiative-Based Learning - An Interdisciplinary Approach - Enrica De Cian; Johannes Buhl; Samuel Carrara; Michela Bevione; Silvia Monetti; Holger Berg (Fondazione Eni Enrico Mattei (FEEM), 2016)
This paper explores the opportunities for integrating Initiative Based Learning (IBL) and Integrated Assessment Models (IAMs) in order to improve our understanding of learning in the context of societal transition pathways, and more specifically by focusing on solar PV as an energy transition technology. Our analysis shows that IAMs and IBL conceptualize learning in a very different way, and the two approaches have major structural differences with respect to the geographical as well as the temporal scale of analysis. This is also due to the different goals of the two methodologies. The aim of IAM is to develop long-term energy and technology scenarios for the next thirty to eighty years, and to describe learning processes mostly to account for future potential improvements in technologies, while IBL focuses on understanding the configuration of actors in specific institutional settings that legitimize and support specific technologies and ultimately lead to dynamics of social learning. Although ambitious forms of integration between IAMs and IBL are not feasible today, the two approaches can be used in parallel and lead to mutual enrichment via a process that we label a two-way recursive collaboration.
Keywords: O31; O33; O35; Q42; 330; Social Learning; Innovation Diffusion; Technology Adoption; Integrated Assessment; Case Study; Transition Research; Initiative-based Learning; Solar PV Learning Curves